Frequency and clinicopathological presentation of gynaecological malignancies - Akhtar, Zubaida; Majid, Anam; Naz, Talat; Jamal, Tanveer; Qazi, Qudsia; Samad, Ambareen (Journal of Postgraduate Medical Institute, 2014)
Objectives: To describe the frequency and clinicopathological presentation ofmalignancies of the female genital tract presenting to a tertiary care hospital.Methodology: This descriptive study was carried out at Department of Obstetricsand Gynaecology, Unit A of Khyber Teaching Hospital, Peshawar fromJanuary 2008 to December 2012. A total of 4657 patients were admittedduring the study period and all the patients having genital tract malignancieswere included. Detailed history was taken and relevant examinations andinvestigations were carried out. Surgical procedures were performed whereneeded and specimens were sent for histopathology. Clinical and surgicalstaging was also carried out. All the details were noted down on a semi-structuredproforma.Results: There were 43 cases of gynaecological malignancies with mean ageof 43.74±15.51 years. Ovarian cancer was the most common (n=22, 51.22%)followed by uterine cancer (n=10, 23.33%). The majority of patients diagnosedwith ovarian cancers (n=9/22, 40.94%) were nulliparous, whereas themajority of uterine and cervical cancers were multiparous (n=7/10, 70.0%) andgrandmultiparous (n=7/9, 77.78%), respectively. Ovarian cancers mostly presentedwith an abdominal mass (n=16/22, 72.7%) while uterine and cervicalcancer presented with irregular cycles (n=7/10, 70.0%) and post coital bleeding(n=4/10, 40%). Advanced stage cancer cases were 19/43 (44.22%). Serouscystadenocarcinoma was the most common ovarian malignancy (n=16/22,72.73%) while endometrioid adenocarcinoma (n=9/10, 90%) was the mostcommon uterine carcinoma and squamous cell carcinoma was the most commoncervical carcinoma (n=7/9, 77.88%).Conclusions: Ovarian cancer was the most commonly encountered malignancyalthough all gynaecological malignancies are rare.